The Impact of the Knowledge-based Economy on the Total Factor Productivity: An Applied Study on the Egyptian Economy During the Period (1990-2022) - Kortam, Sayeda Kamal Ali (The Arab Journal of Administration, 2024)
The study aims to analyze and measure the impact of the knowledge-based economy on the total factor productivity during the period (1990-2022). The study used a set of indicators that express the four basic aspects of the knowledge-based economy as independent variables. The study relied on time series data during the study period, and a number of independent variables were used: information and communications technology, education, innovation, and the economic and institutional system. In addition, gross fixed capital formation as a proportion of GDP as a control variable was included in the standard model. To evaluate the impact of the knowledge-based economy on the total factor productivity, the study relied on the autoregressive distributed lag period (ARDL) methodology. The study found a positive and insignificant effect of public spending on education as a percentage of GDP on total factor productivity, as every increase in public spending on education as a percentage of GDP by 1% leads to an increase in total factor productivity by 0.04%. There is a positive and significant effect of the number of mobile phone lines per 100 population on the total factor productivity, but this effect is small, as is evident from the value of the transactions. Every increase in the number of mobile phone lines per 100 population by 1% leads to an increase in the total factor productivity by 0.006%. The study also found that there is a positive and insignificant effect of the number of patents for residents on the total factor productivity, but this effect is small, as is evident from the value of the coefficients. Whereas, each increase in the number of patents for residents by 1% leads to an increase in the total factor productivity by 0.0002%. There is a negative and significant effect of the total number of Internet users as a percentage of the total population on the total factor productivity, but this effect is small and is evident from the value of transactions. The short-run results show that the total factor productivity is affected by the information and communications technology (ICT) variable only, as there is a negative and insignificant effect of the ICT variable on the total factor productivity in the short run.